Accessibility and the evaluation of investments on the Beijing subway - Haibing Jiang; David M Levinson (Journal of Transport and Land Use)
This study measures the job and population accessibility via transit for Beijing using the cumulative opportunity metric. It is shown that transit accessibility varies widely across Beijing, but is highly focused on subway stations. Early lines added far more accessibility than more recently planned lines.